Optimization of crystal violet photodegradation and investigation of the antibacterial performance by silver-doped titanium dioxide/graphene aerogel nanocomposite. Issue 12 (15th June 2023) - Trinh, Truong Thi Phuong Nguyet Xuan; Trinh, Dinh Ngoc; Cuong, Duong Chi; Hai, Nguyen Duy; Huong, Le Minh; Thinh, Doan Ba; Hoa, Huynh Nhut; Cong, Che Quang; Nam, Nguyen Thanh Hoai; An, Hoang; Khoa, Ta Dang; Viet, Vo Nguyen Dai; et al.
Abstract: In this study, silver-doped titanium dioxide/graphene aerogel (Ag–TiO2 /GA ‒ ATG) was synthesized using the simple hydrothermal method with different Ag contents. The obtained materials were characterized by various modern analytical methods, in which the ATG50 sample, prepared with 50 mg of AgNO3, demonstrated the highest photodegradation performance towards crystal violet (CV). The individual and simultaneous effects of crucial factors, namely pH, CV concentration, catalyst dose, adsorption time, and photodegradation time on the photocatalytic efficiency were evaluated via Plackett-Burman and Box-Behnken models, respectively, which revealed up to 99.95% of removal efficiency at pH 6.5, 25 mg/L of the dye, and 29 mg of catalyst. Besides, ATG50 also achieved notable photodegradation potentials against methylene blue and indigo carmine with 97.11 and 53.22% of elimination, respectively, whilst a sufficient silver release and great reusability were acquired even after the 5th recycling run. And the antibacterial activity of the as-chosen ATG50 was also affirmed against Staphylococcus aureus and Escherichia coli . Therefore, the acquired results elucidate the synthesized ATG material as a promising solution for the treatment of organic dyes in wastewater and antibacterial applications.